2022
DOI: 10.1186/s13071-022-05167-0
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and molecular identification reveals a high diversity of Anopheles species in the forest region of the Cambodia–Laos border

Abstract: Background To develop an effective malaria vector intervention method in forested international border regions within the Greater Mekong Subregion (GMS), more in-depth studies should be conducted on local Anopheles species composition and bionomic features. There is a paucity of comprehensive surveys of biodiversity integrating morphological and molecular species identification conducted within the border of Laos and Cambodia. Methods A total of 23… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 103 publications
1
5
0
Order By: Relevance
“…sinensis sample were paired to determine the species of An. sinensis in accordance with previous studies [ 35 , 36 ] (Additional file 1 : Table S1).…”
Section: Methodssupporting
confidence: 91%
“…sinensis sample were paired to determine the species of An. sinensis in accordance with previous studies [ 35 , 36 ] (Additional file 1 : Table S1).…”
Section: Methodssupporting
confidence: 91%
“…vagus was the dominant species but only 12 An.vagus were randomly investigated by molecular analysis of ITS 2 and the COII sequence: all are not genetically distinct An. vagus -like species [ 38 ] Hasanah et al . 2022 a An.…”
Section: Resultsmentioning
confidence: 99%
“…Likewise, there were no genetically distinct An. vagus -like species in twelve specimens from the border between Laos and Cambodia [ 38 ]. In contrast, studies conducted in East Timor [ 44 ] reported two groups of An.…”
Section: Resultsmentioning
confidence: 99%
“…At present, species identification of mosquitoes mostly relies on morphological identification. However, morphological identification methods are limited by many factors, such as damaged specimens, similar morphology of close-related species, and difficult identification of imported species ( 16 ). More importantly, new mosquito species could become vectors of new diseases, and monitoring of mosquito species in a geographical area is crucial ( 17 ).…”
Section: Discussionmentioning
confidence: 99%